The Role of Woman’s Peer Group in Enhancing Self-Concept and Self-Image Members To Do Aesthetic Procedures in Jakarta - Alexandrina, Elke; Ramonita, Latifa; Wiguna, Maylaffayza; Wempi, J.A (TheJournalish: Social and Government, 2025)
This study investigates the role of women’s social groups in enhancing self-concept and self-image to do aesthetic surgery in Jakarta, Indonesia. The existence of these groups can also play a role as reference group or supporter among members. Based on this situation, this study seeks to reveal the complex interplay between support groups, self-concept, and self-image among women in Jakarta in deciding to have aesthetic procedures. Drawing on qualitative inquiry, the research focuses on the voices and experiences of women who have undergone aesthetic procedures, enhanced by their support groups. Data collected through in-depth interviews to members of women’s peer groups, aesthetic doctors, a psychologist, and also through document analysis. The findings shed light on the nuanced ways in which women in Jakarta negotiate beauty ideals and identity formation within a globalized context. While Korean beauty trends offer a compelling aesthetic ideal, they also raise questions about the commodification of beauty and its impact on self-esteem and body image. By situating these findings within the broader socio-cultural landscape, the research contributes to a deeper understanding of the complex dynamics shaping beauty culture in Jakarta and offers insights into promoting body positivity and empowering individuals to embrace diverse expressions of beauty.